2020
DOI: 10.1186/s12957-020-01939-z
|View full text |Cite
|
Sign up to set email alerts
|

Katanin P60: a potential biomarker for lymph node metastasis and prognosis for non-small cell lung cancer

Abstract: Background: This study aimed to assess the correlation of katanin P60 expression with clinical characteristics and survival profiles of surgical non-small cell lung cancer (NSCLC) patients. Methods: Two hundred and sixty-five primary NSCLC patients treated by surgical resection were retrospectively viewed. The expression of katanin P60 in the tumor specimen was detected by the immunohistochemical (IHC) staining assay. Preoperative clinical data were collected from patients' medical records, and survival data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Both katanin p60 and p80 expression were also significantly correlated with higher lymph node metastasis and shorter overall survival in patients with breast cancer [22,23] . Recently, similar roles of katanin p60 and p80 have also been reported in NSCLC [25,26] . These results clearly show that katanin subunits p60 and p80 are not only highly expressed in cancer tissues, but also play a role in the proliferation, migration, and metastasis of cancer cells, and are related to the prognosis of cancer patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Both katanin p60 and p80 expression were also significantly correlated with higher lymph node metastasis and shorter overall survival in patients with breast cancer [22,23] . Recently, similar roles of katanin p60 and p80 have also been reported in NSCLC [25,26] . These results clearly show that katanin subunits p60 and p80 are not only highly expressed in cancer tissues, but also play a role in the proliferation, migration, and metastasis of cancer cells, and are related to the prognosis of cancer patients.…”
Section: Discussionsupporting
confidence: 58%
“…Elevated expression of katanin p60 has been shown during prostate cancer progression and may contribute to cancer metastasis [21] . Similarly, both katanin subunits p60 and p80 have been found to be correlated with lymph node metastasis and worse prognosis in breast cancer [22–24] and non-small cell lung cancer (NSCLC) [25,26] . In particular, it has recently been reported that compared with adjacent PTC tissues, both are highly expressed in tumor tissues [27] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the moleculer pathogenesis still need to be further explored. It has been identified that Katanin P60 is a potential biomarker for lymph node metastasis and prognosis for non-small cell lung cancer [ 26 ]. Moreover, circular RNAs are reported to play an essential role in the progression of human lung cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated expression of KATNB1 shares a similar positive correlation with advanced breast cancer staging, lymph node metastasis, and reduced rates of overall survival in patients ( Table 1 ; Li et al, 2018 ). Additionally, in non-small cell lung cancer (NSCLC), the elevated expression of KATNA1 and KATNB1 correlates with lymph node metastasis and advanced tumor progression ( Table 1 ; Wang et al, 2020 ; Ye et al, 2020 ). Katanin expression is also dysregulated in other types of cancers like papillary thyroid carcinoma (PTC), where both KATNA1 and KATNB1 are highly expressed in tumors and tumor-adjacent tissues; furthermore, elevated katanin expression correlates with advanced PTC staging and worse disease-free survival in patients ( Chen et al, 2020 ).…”
Section: Katanin Dysfunction In Cancermentioning
confidence: 99%
“…Katanins function by harnessing the energy produced from ATP hydrolysis to drive microtubule-severing events ( McNally and Vale, 1993 ; McNally and Thomas, 1998 ). Due to their role in facilitating cytoskeletal rearrangements, the katanins have become the subject of intense research in the fields of neuroscience ( Banks et al, 2018 ), cancer ( Wang et al, 2020 ), and cell and structural biology ( Willsey et al, 2018 ; Faltova et al, 2019 ; Korulu and Yildiz, 2020 ).…”
Section: Introductionmentioning
confidence: 99%